Political Processes and Social Moralities in Chile (1990–2024) - Araujo-Kakiuchi, K (John Wiley and Sons Inc, 2026)
Recent political events in Chile— a 2019 social outburst, attempted constitution-making processes ending in rejection, and electoral volatility—have raised questions about the reasons behind seemingly contradictory aspects of these phenomena. This article addresses these questions by analysing the relationship between social moralities and politics. Based on empirical research, it argues that an initial phase of relative autonomy of these two spheres has been followed by a stage of deep interconnection between them. This shift has fuelled individuals moral critiques and detachment from institutional political dynamics, a conjunction that has created a context of high volatility, rejection and scarce ideological and electoral loyalty. © 2025 Society for Latin American Studies.